Immunometabolism in the pathogenesis of vitiligo - Lyu, Chen; Sun, Yonghu (Frontiers in Immunology, 2022)
Vitiligo is a common depigmenting skin disorder characterized by the selective loss of melanocytes. Autoimmunity, genetic, environmental, and biochemical etiology has been proposed in vitiligo pathogenesis. However, the exact molecular mechanisms of vitiligo development and progression are unclear, particularly for the immunometabolism. Sporadic studies have suggested mitochondrial dysfunction, enhanced oxidative stress, and specific defects in other metabolic pathways can promote dysregulation of innate and adaptive immune responses in vitiligo. These abnormalities appear to be driven by genetic and epigenetic factors modulated by stochastic events. In addition, glucose and lipid abnormalities metabolism have been associated with vitiligo. Specific skin cell populations also involved in the critical role of dysregulation of metabolic pathways, including keratinocytes, tissue-resident memory T cells, and innate lymphoid cells in vitiligo pathogenesis. Novel therapeutic treatment also raised based on the abnormalities of immunometabolism. This review summarizes the current knowledge on immunometabolism reprogramming in the pathogenesis of vitiligo and novel treatment options.